Effective LARC Providers: Moving Beyond Training (Republication) - Shelton, James D (Glob Health Sci Pract, 2016)
Effective and productive providers are the key to successful provision of long-acting reversible contraceptives (LARCs). But LARCs demand more of providers than short-acting resupply methods. In addition to sound training, key elements to developing highly productive providers of LARCs include a thorough understanding of the service delivery system context; selecting providers with the most potential, especially from mid-level cadres; strong mentoring and supportive supervision; and attention to the supply chain and to demand-side support.